p53-targeted cancer pharmacotherapy: move towards small molecule compounds - Kim, S.; Dass, Crispin (John Wiley & Sons Ltd., 2011)
Objectives For the past three decades of research, p53 has been identified as one of the most targetable molecules for developing anticancer treatments. This tumour suppressor protein is involved in apoptosis, cell cycle arrest and senescence. A wide range of pharmaceutical drugs and radiotherapy treatments activate this protein and rely on p53 signalling for therapeutic outcome. Promising small molecular weight compounds, some of which are undergoing clinical trials, are discussed in this review. Key findings The spectrum of potential therapeutic approaches trialled for p53 stretch from gene therapy to the more recent development of small molecules capable of activating wild-type p53 or reactivating mutant p53. Summary Our ever-growing knowledge leads us to better understand this protein, from its structure and activities to its potential therapeutic application, firstly for cancer and then for other diseases and maybe even for reversal of ageing.